Teaching lab-based courses remotely: approaches, technologies, challenges, and ethical issues - Attarbashi, Zainab; Hassan Abdalla Hashim, Aisha; Abuzaraida, Mustafa Ali; Khalifa, Othman Omran; Mustafa, Manar (IIUM Press, 2021)
As the Massive Open Online Courses (MOOC) became widely popular since the last decade, online learning has acquired substantial traction. Then, as the Covid-19 pandemic started, this method of education became indispensable. All educational institutes all around the world were compelled to switch to online classes as a safer and more flexible option. Many studies were made to examine the effectiveness of this online mode education. However, more aspects are to be studied about the virtual laboratories, which are important way to convey practical skills and comprehend complicated theories for science and engineering subjects. Each approach in online mode has advantages and disadvantages, and it lacks some of the qualities of actual experiments seen in traditional learning methods, such as soft skills obtained from teamwork, the ability to assess levels of knowledge and contentment, the level of attention and absorption. The goal of this research is to address these issues in order to achieve the longterm goals and learning outcomes of STEM education. Technologies used by different educational institutes as a substitute for physical laboratories is also discussed such as gaming and Virtual reality. Lastly, some of the ethical issues related to online learning are addressed.